Sex chromosome evolution in fish: the formation of the neo-Y chromosome in Eigenmannia (Gymnotiformes) - Almeida-Toledo, L. F.; Foresti, F.; Daniel, MFZ; Toledo, S. A. (Springer, 2000)
Chromosomes of a species of Eigenmannia presenting a X1X1X2X2:X1X2Y sex chromosome system, resulting from a Y-autosome Robertsonian translocation, were analyzed using the C-banding technique, chromomycin A(3) (CMA(3)) and mithramycin (MM) staining and in situ digestion by the restriction endonuclease AluI. A comparison of the metacentric Y chromosome of males with the corresponding acrocentrics in females indicated that a C-band-positive, CMA(3)/MM-fluorescent and AluI digestion-resistant region had been lost during the process of translocation, resulting in a diminution of heterochromatin in the males. It is hypothesized that the presence of a smaller amount of G+C-rich heterochromatin in the sex chromosomes of the heteromorphic sex when compared with the homomorphic sex may be associated with the sex determination mechanism in this species and may be a more widely occurring phenomenon in fish with differentiated sex chromosomes than was initially thought.